Thermodynamic analysis of the solubility of propranolol-HCl in ethanol + water mixtures (2010)
Propranolol-HCl (PPN-HCl) is a non selective ?-adrenergic blocker widely used in therapeutics. Nevertheless, their physicochemical properties in aqueous media have not been adequately studied. In this context, by using the van't Hoff and Gibbs equations t